Influence of installation height of a submersible mixer on solid‒liquid two‒phase flow field - Tian, Fei; Zhang, Erfeng; Yang, Chen; Sun, Dehua; Shi, Weidong; Chen, Yonghua (Frontiers in Energy Research, 2023)
With the increasingly severe situation of water pollution control, optimal design of the mixing flow field of submersible mixers and improving the mixing uniformity of activated sludge have become key research issues. This paper presented numerical simulations of the solid-liquid two-phase flow problem at various installation heights based on the coupled CFD-DEM method in the Eu-ler-Lagrange framework. The velocity distribution, dead zones distribution, particles' velocity development, particles' mixing degree, and particles' aggregation of the flow field were compared and analyzed for different installation heights. The results show that the flow field has two flow patterns: single- and double-circulation, due to different installation heights, in which the velocity and turbulent kinetic energy of the flow field of the double-circulation flow pattern are more uniform. The installation height affects the moment particles enter the impeller and the core jet zone, thus affecting the degree of particle mixing and the mixing time. The adjustment of the installation height also has an impact on particle aggregation. These findings indicate that the installation height significantly affects the flow field characteristics and the particle motion distribution. The coupled CFD-DEM method can analyze the macroscopic phenomenon of the solid-liquid two-phase flow field of the submersible mixer from the scale of micro-scopic particles, which provides a theoretical approach for the optimal design of the mixing flow field. It can provide better guidance for engineering practice.